Environmentally friendly sampling swab and preparation method thereof
By designing an environmentally friendly sampling swab using composite fiber material and hollow structure, the problems of user discomfort and post-treatment contamination caused by traditional swabs during use are solved, and a more efficient biological sample collection and environmentally friendly treatment method is achieved.
Patent Information
- Application Number
- CN202410930545.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-11
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-07-11
AI Technical Summary
Existing sampling swabs will cause discomfort to users during use, and the pollution problems caused by their treatment are difficult to solve, including the incineration to produce toxic substances, landfill occupies land and high chemical treatment costs.
An environmentally friendly sampling swab is designed, including an inner swab rod, an outer swab rod, an outer sampling head and an inner sampling head. It adopts hollow structure and composite fiber material. The inner swab rod is made of polylactic acid, bamboo fiber and coconut fiber. The outer swab rod is made of sodium alginate, tapioca starch and anhydrous calcium chloride, and has good mechanical properties and degradability.
This environmentally friendly sampling swab is better than traditional swabs in terms of mechanical properties, can collect biological samples more effectively, and has good degradability after treatment, reducing environmental pollution.
Smart Images

Figure CN118512214B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of swabs, and in particular to an environmentally friendly sampling swab and a preparation method thereof. Background Art
[0002] The swab is mainly composed of two parts, the swab stick and the swab head. The swab head is in direct contact with the subject. The stick is mainly made of polymer materials, thin in the front and thick in the back. In order to facilitate the breakage after sampling, a fine cut is often made 1 cm near the sampling end of the swab. After sampling, it is broken and immersed in the test solution. The swab head is mostly made of polymer synthetic fibers such as polyester and polyamide through different processes.
[0003] The method of using the sampling swab is: the user inserts the sampling swab into the inside of the mouth, throat or nose. In order to ensure the accuracy of the test results, try to insert it into the deeper area of the mouth, throat or nose, repeatedly scrape the inner wall of the mouth, throat or nose many times, then change the deeper area of the mouth, throat or nose to another place, and repeatedly scrape it many times to obtain accurate biological sample sampling results. After sampling, the sampling swab is sealed and stored.
[0004] During the sampling process, a considerable number of users will feel uncomfortable, and some users may even feel like vomiting. This is the current problem.
[0005] After the sampling is completed, since the sampling swab is a disposable product and cannot be reused, the disposal of the sampling swab becomes a big problem. If the incineration method is adopted, toxic substances such as furan and dioxin will be produced, polluting the environment; if the landfill method is adopted, a large amount of land will be occupied, and the existing sampling swabs cannot be decomposed, polluting the soil and water sources; if the chemical treatment method is adopted, additional costs will be incurred, and the by-products will also need to be handled, which is not economically cost-effective. Summary of the invention
[0006] In view of this, the present invention proposes an environmentally friendly sampling swab and a preparation method thereof.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] An environmentally friendly sampling swab comprises an inner swab rod, an outer swab rod, an outer sampling head and an inner sampling head; the outer sampling head is fixedly provided at the upper end of the outer swab rod; the outer swab rod and the outer sampling head are hollow structures; the inner swab rod is embedded inside the outer swab rod; the sampling end of the outer sampling head is provided with a plurality of sampling grooves at a certain interval; the inner sampling head is arranged inside the sampling outer head; the sampling end of the inner sampling head is fixedly provided with a plurality of sampling convex portions at a certain interval; a plurality of sampling convex portions are respectively penetrated and extend out of a plurality of sampling grooves; the sampling convex portions slightly extend out of the sampling grooves.
[0009] Furthermore, the inner swab rod comprises the following raw materials in parts by weight: 95-105 parts of polylactic acid, 4-10 parts of polyhydroxyalkanoate, 15-40 parts of bamboo fiber, 5-8 parts of coconut shell fiber, 0.3-3 parts of silane coupling agent, 0.5-7 parts of maleic anhydride, and 0.2-0.8 parts of dicumyl peroxide;
[0010] The outer swab rod and the outer sampling head include the following raw materials in parts by weight: 3 to 10 parts of sodium alginate, 30 to 90 parts of cassava starch and 15 to 45 parts of anhydrous calcium chloride;
[0011] The inner swab rod is made of cellulose aerogel.
[0012] Furthermore, the preparation method of the inner swab rod is as follows:
[0013] Drying: Place bamboo fiber, coconut shell fiber, polylactic acid and polyhydroxyalkanoate in a constant temperature drying oven and fully dry them at a drying temperature of 60 to 90°C for 20 to 30 hours;
[0014] Composite fiber synergistic surface modification, alkali treatment:
[0015] Add the dried bamboo fiber and coconut shell fiber to a 5% sodium hydroxide solution according to a certain solid-liquid ratio, mix thoroughly, soak at room temperature for 10 to 15 hours, filter out, wash with deionized water until neutral, and dry thoroughly in a drying oven at a temperature of 70 to 80°C for 6 to 8 hours.
[0016] Composite biodegradable materials synergistic surface modification, silane coupling agent modification:
[0017] The silane coupling agent KH560 is added to the mixture of ethanol and water in a certain volume ratio, and the pH thereof is adjusted to 5 with acetic acid, and the mixture is fully stirred with a magnetic stirrer. When no floccules appear in the mixture, the hydrolysis is completed; the alkali-treated and dried bamboo fiber and coconut shell fiber are added to the hydrolysis solution in a certain ratio, and the mixture is fully stirred again with a magnetic stirrer. After the stirring is completed, the mixture is placed in a ventilated place to wait for the volume to completely evaporate;
[0018] Graft modification of polylactic acid and polyhydroxyalkanoate:
[0019] Take maleic anhydride and dicumyl peroxide, dissolve them in a certain amount of acetone, the amount of acetone is appropriate to completely dissolve maleic anhydride and dicumyl peroxide; then add polylactic acid and polyhydroxyalkanoate, wait for the solvent to evaporate completely, use a torque rheometer to perform melt mixing, the mixing temperature is 170-185°C, the rotation speed is 30 r / min, the mixing time is 12-15min, and finally obtain a graft copolymer product;
[0020] Extrusion molding:
[0021] The composite fiber that has undergone synergistic surface modification and the graft copolymer product that has been modified with a silane coupling agent are respectively placed into the two feed ports of a twin-screw extruder, and appropriate feed speeds and screw speeds are set. The temperature from the feed port to the mold outlet in the twin-screw extruder is set to 165-175°C. Finally, degradable high-strength strips are made and processed to form inner swab rods.
[0022] Furthermore, in the alkali treatment, the solid-liquid ratio of the dried bamboo fiber and coconut shell fiber to the sodium hydroxide solution is 1:15-20.
[0023] Furthermore, in the silane coupling agent modification, the volume ratio of silane coupling agent KH560: ethanol and water mixed liquid is 1:6-15.
[0024] Furthermore, in the modification with silane coupling agent, the solid-to-liquid ratio of the alkali-treated and dried bamboo fiber and coconut shell fiber to the hydrolysis solution is 1:5-8.
[0025] Furthermore, the preparation method of the outer swab rod and the outer sampling head is as follows:
[0026] Preparation of sodium alginate solution:
[0027] Sodium alginate is added into deionized water according to a certain solid-liquid ratio, and the sodium alginate solution is stirred evenly using a magnetic stirrer;
[0028] Sodium alginate solution and tapioca starch mixing:
[0029] Adding cassava starch to the sodium alginate solution, and stirring the mixture of cassava starch and the sodium alginate solution uniformly with a magnetic stirrer; placing the mixture of cassava starch and the sodium alginate solution on a heating platform for heating at a temperature of 60 to 80° C. for 30 minutes to 1 hour until the mixture is fully mixed and becomes uniform; and then placing it under ultrasonic vibration to remove bubbles;
[0030] Preparation of calcium chloride solution:
[0031] Add anhydrous calcium chloride to deionized water according to a certain solid-liquid ratio, and stir thoroughly with a magnetic stirrer; stir the anhydrous calcium chloride and deionized water thoroughly at room temperature for 15 to 30 minutes; place them under ultrasonic vibration to remove bubbles and wait for them to return to normal temperature;
[0032] Prepare the outer swab shaft and outer sampling tip:
[0033] After the preparation of sodium alginate solution and calcium chloride solution is completed, the prepared cassava starch / sodium alginate / calcium chloride solution is mixed evenly, degassed and poured into a mold, and left for a period of time to obtain a strip gel; then heated in a 60-80°C water bath for 15-30 minutes, and then the excess calcium chloride solution on the surface of the strip gel is washed off with deionized water, and then soaked in deionized water for 12-15 hours; finally, the soaked strip gel is placed in a freezer, the freezing temperature is -20--30°C, the freezing time is 12-18 hours, and after freeze-drying, a strip hydrogel with good mechanical properties is obtained, which is processed into an external swab rod and an external sampling head.
[0034] Furthermore, in the preparation of the sodium alginate solution, the solid-liquid ratio of sodium alginate and deionized water is 0.03-0.1:1.
[0035] Furthermore, in the preparation of the calcium chloride solution, the solid-liquid ratio of anhydrous calcium chloride and deionized water is 0.05-0.15:1.
[0036] The present invention also provides a method for preparing an environmentally friendly sampling swab, comprising the following steps:
[0037] S1: Sampling swab assembly
[0038] The prepared inner sampling head is placed inside the outer sampling head; the sampling convex parts of the inner sampling head are respectively penetrated with a plurality of the sampling grooves; the outer part of the sampling convex parts of the inner sampling head slightly extends out of the sampling grooves; the outer sampling rod and the outer swab head are connected by glue; finally, the inner swab rod is tightly inserted into the inner part of the outer swab rod, and the inner swab rod and the inner sampling head are in contact;
[0039] S2: Human body sampling
[0040] When in use, hold the external sampling swab, insert the external sampling head into the human body's oropharynx, throat and nose, make the internal sampling head close to the inner wall of the oropharynx and nose, rotate along the inner wall of the oropharynx and nose for several circles to complete the sampling; then take out the sampling swab and seal it for storage;
[0041] S3: Sample collection
[0042] When detecting and analyzing the sampling swab, the inner swab rod of each sampling swab is slid toward the inner sampling head with the help of a tool, and the inner swab rod continuously squeezes the inner sampling head to squeeze out the sample collected on the inner sampling head, so as to facilitate subsequent sample detection and analysis;
[0043] S4: Sampling completed swab processing
[0044] The sampling swabs after sample extrusion are collected and processed centrally.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) The environmentally friendly sampling swab prepared by the present invention has an inner swab rod with much better tensile strength, bending strength and impact strength than those of conventional sampling swabs, and is suitable for being made into a strip material for use in the sampling swab, thereby ensuring the shape, toughness and hardness of the sampling swab, and also ensuring that the inner swab rod can be well abutted against the inner sampling head, and squeeze out the biological samples collected on the sampling convex part of the inner sampling head and the outer sampling head for detection, thereby expanding the amount of samples collected and facilitating obtaining more accurate sampling detection results;
[0047] (2) The environmentally friendly sampling swab prepared by the present invention has good mechanical properties, good water retention performance, is suitable for being made into strip materials, and has a certain elasticity for use in the sampling swab, ensuring that the outer swab rod and the outer sampling head in the sampling swab have a certain softness, which is convenient for tight fitting and pressing the inner swab rod;
[0048] (3) The environmentally friendly sampling swab prepared by the present invention has a plurality of sampling convex parts, which expands the sampling surface area and facilitates the collection of more biological samples. The user inserts the environmentally friendly sampling swab into the mouth, throat or nose and closes to the inner wall, and rotates it a few times. There is no need to poke it deep into the mouth, throat or nose or everywhere, and there is no need to repeatedly scrape the inner wall. While improving the user's comfort, it also reduces the sampling time; the plurality of sampling convex parts have good water absorption performance, better elasticity than the external sampling head, and less tensile strength than the external sampling head. Therefore, when the user collects samples in the mouth, throat or nose, the plurality of sampling convex parts will quickly absorb the biological sample. When the sampling convex parts are squeezed by the inner swab rod, the biological sample collected on the inner sampling head will be quickly squeezed out, which is convenient for detection;
[0049] (4) The inner swab rod, outer swab rod, outer sampling head and inner sampling head of the environmentally friendly sampling swab prepared by the present invention all have good degradability. After the sampling swab collection work is completed, when the sampling swab is collected and processed, the processing process is simpler and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 A schematic cross-sectional view of a sampling swab provided by an embodiment of the present invention;
[0051] Figure 2 for Figure 1 Enlarged view of point A in .
[0052] In the figure: 1. inner swab rod; 2. outer swab rod; 3. outer sampling head; 4. inner sampling head; 41. sampling convex part. DETAILED DESCRIPTION
[0053] The technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0054] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0055] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0056] Preparation Example 1-1
[0057] An inner swab rod, the preparation method of which is as follows:
[0058] Drying: Take 1.5kg of bamboo fiber and 0.5kg of coconut shell fiber; place the bamboo fiber, coconut shell fiber, polylactic acid and polyhydroxyalkanoate in a constant temperature drying oven and fully dry them at a drying temperature of 80°C for 20 hours;
[0059] Composite fiber synergistic surface modification, alkali treatment:
[0060] The dried bamboo fiber and coconut shell fiber were added into 5% sodium hydroxide solution at a solid-liquid ratio of 1:15, mixed thoroughly, and then soaked at room temperature for 12 hours. After filtering and taking out, they were washed with deionized water until neutral, and then placed in a drying oven for thorough drying at a temperature of 80°C for 8 hours.
[0061] Composite biodegradable materials synergistic surface modification, silane coupling agent modification:
[0062] Take 9.5kg of polylactic acid, 0.4kg of polyhydroxyalkanoate, and 0.03kg of silane coupling agent; add silane coupling agent KH560 to a mixture of ethanol and water at a volume ratio of 1:10, adjust the pH to 5 with acetic acid, and stir it thoroughly with a magnetic stirrer. When no flocs appear in the mixture, the hydrolysis is completed; add alkali-treated and dried bamboo fiber and coconut shell fiber to the hydrolysis solution at a ratio of 1:5, and stir it thoroughly with a magnetic stirrer again. After stirring, place it in a ventilated place and wait for the volume to completely evaporate;
[0063] Graft modification of polylactic acid and polyhydroxyalkanoate:
[0064] Take 0.05kg of maleic anhydride and 0.03kg of dicumyl peroxide; dissolve maleic anhydride and dicumyl peroxide in a certain amount of acetone, and the amount of acetone is appropriate to completely dissolve maleic anhydride and dicumyl peroxide; then add polylactic acid and polyhydroxyalkanoate, wait for the solvent to evaporate completely, and use a torque rheometer to perform melt mixing, the mixing temperature is 180°C, the rotation speed is 30 r / min, and the mixing time is 12min, and finally a graft copolymer product is obtained;
[0065] Extrusion molding:
[0066] The composite fiber that has undergone synergistic surface modification and the graft copolymer product that has been modified with a silane coupling agent are respectively placed into the two feed ports of a twin-screw extruder, and appropriate feed speeds and screw speeds are set. The temperature from the feed port to the mold outlet in the twin-screw extruder is set to 165-175°C. Finally, degradable high-strength strips are made and processed to form inner swab rods.
[0067] Preparation Example 1-2
[0068] An inner swab rod, the preparation method of which is as follows:
[0069] Drying: Take 4kg of bamboo fiber and 0.88kg of coconut shell fiber; place the bamboo fiber, coconut shell fiber, polylactic acid and polyhydroxyalkanoate in a constant temperature drying oven and fully dry them at a drying temperature of 80°C for 20 hours;
[0070] Composite fiber synergistic surface modification, alkali treatment:
[0071] The dried bamboo fiber and coconut shell fiber were added into 5% sodium hydroxide solution at a solid-liquid ratio of 1:15, mixed thoroughly, and then soaked at room temperature for 12 hours. After filtering and taking out, they were washed with deionized water until neutral, and then placed in a drying oven for thorough drying at a temperature of 80°C for 8 hours.
[0072] Composite biodegradable materials synergistic surface modification, silane coupling agent modification:
[0073] Take 10.5kg of polylactic acid, 1kg of polyhydroxyalkanoate, and 0.05kg of silane coupling agent; add silane coupling agent KH560 to a mixture of ethanol and water at a volume ratio of 1:10, adjust the pH to 5 with acetic acid, and stir it thoroughly with a magnetic stirrer. When no flocs appear in the mixture, the hydrolysis is completed; add alkali-treated and dried bamboo fiber and coconut shell fiber to the hydrolysis solution at a ratio of 1:5, and stir it thoroughly with a magnetic stirrer again. After stirring, place it in a ventilated place and wait for the volume to completely evaporate;
[0074] Graft modification of polylactic acid and polyhydroxyalkanoate:
[0075] Take 0.1kg of maleic anhydride and 0.05kg of dicumyl peroxide; dissolve maleic anhydride and dicumyl peroxide in a certain amount of acetone, and the amount of acetone is appropriate to completely dissolve maleic anhydride and dicumyl peroxide; then add polylactic acid and polyhydroxyalkanoate, wait for the solvent to evaporate completely, and use a torque rheometer to perform melt mixing, the mixing temperature is 180°C, the rotation speed is 30 r / min, and the mixing time is 15min, and finally a graft copolymer product is obtained;
[0076] Extrusion molding:
[0077] The composite fiber that has undergone synergistic surface modification and the graft copolymer product that has been modified with a silane coupling agent are respectively placed into the two feed ports of a twin-screw extruder, and appropriate feed speeds and screw speeds are set. The temperature from the feed port to the mold outlet in the twin-screw extruder is set to 165-175°C. Finally, degradable high-strength strips are made and processed to form inner swab rods.
[0078] Preparation Example 2-1
[0079] An external swab rod and an external sampling head, the preparation method of which is as follows:
[0080] Preparation of sodium alginate solution:
[0081] Take 0.3 kg of sodium alginate, add the sodium alginate into deionized water at a solid-liquid ratio of 0.05:1, and stir the sodium alginate solution evenly with a magnetic stirrer;
[0082] Sodium alginate solution and tapioca starch mixing:
[0083] Take 3 kg of cassava starch, add cassava starch to the sodium alginate solution, and stir the mixture of cassava starch and sodium alginate solution evenly with a magnetic stirrer; place the mixture of cassava starch and sodium alginate solution on a heating platform for heating at a temperature of 80° C. for 30 min until the mixture is fully mixed and becomes evenly mixed; then place it under ultrasonic vibration to remove bubbles;
[0084] Preparation of calcium chloride solution:
[0085] Take 1.5 kg of anhydrous calcium chloride, add the anhydrous calcium chloride into deionized water at a solid-liquid ratio of 0.01:1, and stir thoroughly with a magnetic stirrer; stir the anhydrous calcium chloride and deionized water thoroughly at room temperature for 20 minutes; place them under ultrasonic vibration to remove bubbles and wait for them to return to normal temperature;
[0086] Prepare the outer swab shaft and outer sampling tip:
[0087] After the preparation of sodium alginate solution and calcium chloride solution is completed, the prepared cassava starch / sodium alginate / calcium chloride solution is mixed evenly, degassed and poured into a mold, and left for a period of time to obtain a strip gel; then heated in an 80°C water bath for 30 minutes, and then the excess calcium chloride solution on the surface of the strip gel is washed off with deionized water, and then soaked in deionized water for 12 hours; finally, the soaked strip gel is placed in a freezer, the freezing temperature is -20 to -30°C, the freezing time is 12 hours, and after freeze-drying, a strip hydrogel with good mechanical properties is obtained, which is processed into an external swab rod and an external sampling head.
[0088] Preparation Example 2-2
[0089] An external swab rod and an external sampling head, the preparation method of which is as follows:
[0090] Preparation of sodium alginate solution:
[0091] Take 0.5 kg of sodium alginate, add the sodium alginate into deionized water at a solid-liquid ratio of 0.05:1, and stir the sodium alginate solution evenly with a magnetic stirrer;
[0092] Sodium alginate solution and tapioca starch mixing:
[0093] Take 6 kg of cassava starch, add it to the sodium alginate solution, and stir the mixture of cassava starch and sodium alginate solution evenly with a magnetic stirrer; place the mixture of cassava starch and sodium alginate solution on a heating platform for heating at 80°C for 30 minutes until the mixture is fully mixed and becomes even; then place it under ultrasonic vibration to remove bubbles;
[0094] Preparation of calcium chloride solution:
[0095] Take 3 kg of anhydrous calcium chloride, add the anhydrous calcium chloride into deionized water at a solid-liquid ratio of 0.01:1, and stir thoroughly with a magnetic stirrer; stir the anhydrous calcium chloride and deionized water thoroughly at room temperature for 15 minutes; place them under ultrasonic vibration to remove bubbles and wait for them to return to normal temperature;
[0096] Prepare the outer swab shaft and outer sampling tip:
[0097] After the preparation of sodium alginate solution and calcium chloride solution is completed, the prepared cassava starch / sodium alginate / calcium chloride solution is mixed evenly, degassed and poured into a mold, and left for a period of time to obtain a strip gel; then heated in an 80°C water bath for 20 minutes, and then the excess calcium chloride solution on the surface of the strip gel is washed off with deionized water, and then soaked in deionized water for 12 hours; finally, the soaked strip gel is placed in a freezer, the freezing temperature is -20 to -30°C, the freezing time is 12 hours, and after freeze-drying, a strip hydrogel with good mechanical properties is obtained, which is processed into an external swab rod and an external sampling head.
[0098] Comparative Example 1
[0099] An inner swab rod, compared with Preparation Example 1-1, the difference is that: no composite fiber collaborative surface modification, no alkali treatment step, no composite degradable material collaborative surface modification, no silane coupling agent modification step, and the rest is the same as Preparation Example 1-1;
[0100] Comparative Example 2
[0101] An inner swab rod, compared with Preparation Example 1-1, the difference is that: the grafting modification step of polylactic acid and polyhydroxyalkanoate is not performed, and the rest is the same as Preparation Example 1-1;
[0102] Comparative Example 3
[0103] An external swab rod and an external sampling head, compared with Preparation Example 2-1, the difference is that no sodium alginate is added to the raw materials. That is, the sodium alginate solution preparation step and the sodium alginate solution and cassava starch mixing step are not performed, and cassava starch is directly added to the calcium chloride solution. The remaining preparation conditions and parameters are the same as those of Preparation Example 2-1. The specific method is as follows;
[0104] Preparation of calcium chloride solution:
[0105] Take 1.5 kg of anhydrous calcium chloride, add the anhydrous calcium chloride into deionized water at a solid-liquid ratio of 0.01:1, and stir thoroughly with a magnetic stirrer; stir the anhydrous calcium chloride and deionized water thoroughly at room temperature for 15 minutes; place them under ultrasonic vibration to remove bubbles and wait for them to return to normal temperature;
[0106] Prepare the outer swab shaft and outer sampling tip:
[0107] Take 3kg of cassava starch, and after the calcium chloride solution is prepared, mix the cassava starch and calcium chloride solution evenly, degas and pour them into a mold, and leave them for a while to obtain a strip gel; then heat it in an 80℃ water bath for 20min, then rinse off the excess calcium chloride solution on the surface of the strip gel with deionized water, and then soak it in deionized water for 12h; finally, place the soaked strip gel in a freezer, the freezing temperature is -20~-30℃, the freezing time is 12h, and after freeze-drying, a strip hydrogel with good mechanical properties is obtained, which is processed into an external swab rod and an external sampling head.
[0108] Comparative Example 4
[0109] An external swab rod and an external sampling head, compared with Preparation Example 2-2, the difference is that: sodium alginate is not added to the raw materials. That is, the sodium alginate solution preparation step and the sodium alginate solution and cassava starch mixing step are not performed, and cassava starch is directly added to the calcium chloride solution. The remaining preparation conditions and parameters are the same as those of Preparation Example 2-2. The specific method is as follows;
[0110] Preparation of calcium chloride solution:
[0111] Take 3 kg of anhydrous calcium chloride, add the anhydrous calcium chloride into deionized water at a solid-liquid ratio of 0.01:1, and stir thoroughly with a magnetic stirrer; stir the anhydrous calcium chloride and deionized water thoroughly at room temperature for 15 minutes; place them under ultrasonic vibration to remove bubbles and wait for them to return to normal temperature;
[0112] Prepare the outer swab shaft and outer sampling tip:
[0113] Take 6 kg of cassava starch, and after the calcium chloride solution is prepared, mix the cassava starch and calcium chloride solution evenly, degas and pour them into a mold, and leave them for a while to obtain a strip gel; then heat it in an 80°C water bath for 20 minutes, then rinse off the excess calcium chloride solution on the surface of the strip gel with deionized water, and then soak it in deionized water for 12 hours; finally, place the soaked strip gel in a freezer, the freezing temperature is -20 to -30°C, the freezing time is 12 hours, and after freeze-drying, a strip hydrogel with good mechanical properties is obtained, which is processed into an external swab rod and an external sampling head.
[0114] Example 1
[0115] like Figure 1-2 As shown, an environmentally friendly sampling swab includes an inner swab rod 1, an outer swab rod 2, an outer sampling head 3 and an inner sampling head 4. The inner swab rod 1 in this embodiment adopts the inner swab rod 1 prepared in Preparation Example 1-1, and the outer swab rod 2 and the outer sampling head 3 adopt the outer swab rod 2 and the outer sampling head 3 prepared in Preparation Example 2-1. The inner sampling head 4 is made of CNFs / CA / CMC-Na aerogel on the market.
[0116] An outer sampling head 3 is fixedly provided at the upper end of the inner and outer swab rods 2; the outer swab rod 2 and the outer sampling head 3 are hollow structures; the inner swab rod 1 is embedded inside the outer swab rod 2; a plurality of sampling grooves are provided at a certain interval at the sampling end of the outer sampling head 3; the inner sampling head 4 is arranged inside the outer sampling head; a plurality of sampling protrusions 41 are fixedly provided at the sampling end of the inner sampling head 4 at a certain interval; a plurality of sampling protrusions 41 are respectively penetrated and extend out of a plurality of sampling grooves; the sampling protrusions 41 slightly extend out of the sampling grooves.
[0117] Place the inner sampling head 4 inside the outer sampling head 3; the sampling protrusions 41 of the inner sampling head 4 are respectively penetrated and extend out of several sampling grooves; the outside of the sampling protrusions 41 of the inner sampling head 4 slightly extends out of the sampling grooves; the outer sampling rod and the outer swab head are connected with glue; finally, the inner swab rod 1 is tightly inserted into the inside of the outer swab rod 2, and the inner swab rod 1 and the inner sampling head 4 are abutted.
[0118] When in use, hold the external sampling swab and insert the external sampling head 3 into the human mouth, throat or nose (select one part from the mouth, throat or nose, which can be suitable for sampling in different parts), so that the internal sampling head 4 is close to the inner wall of the oropharynx and nose, and rotate along the inner wall of the oropharynx and nose for several circles to complete the sampling; then take out the sampling swab and seal it for storage.
[0119] When detecting and analyzing the sampling swab, the inner swab rod 1 of each sampling swab is slid toward the inner sampling head 4 with the help of a tool, and the inner swab rod 1 continues to squeeze the inner sampling head 4 to squeeze out the sample collected on the inner sampling head 4, so as to facilitate subsequent sample detection and analysis.
[0120] The sampling swabs after sample extrusion are collected and processed centrally.
[0121] Example 2
[0122] An environmentally friendly sampling swab, which differs from Example 1 in that the inner swab rod in this example adopts the inner swab rod prepared in Preparation Example 1-2, and the outer swab rod and the outer sampling head adopt the outer swab rod and the outer sampling head prepared in Preparation Example 2-1, and the rest are the same as Example 1.
[0123] Example 3
[0124] An environmentally friendly sampling swab, which differs from Example 1 in that the inner swab rod in this example adopts the inner swab rod prepared in Preparation Example 1-2, and the outer swab rod and the outer sampling head adopt the outer swab rod and the outer sampling head prepared in Preparation Example 2-2, and the rest are the same as Example 1.
[0125] Example 4
[0126] An environmentally friendly sampling swab, which differs from Example 1 in that the inner swab rod in this example adopts the inner swab rod prepared in Preparation Example 1-1, and the outer swab rod and the outer sampling head adopt the outer swab rod and the outer sampling head prepared in Preparation Example 2-2, and the rest are the same as Example 1.
[0127] Example 5
[0128] An environmentally friendly sampling swab is disclosed, which differs from Example 1 in that an inner swab rod in this example adopts the inner swab rod prepared in Comparative Example 1, and the rest is the same as Example 1.
[0129] Example 6
[0130] An environmentally friendly sampling swab is disclosed, which differs from Example 1 in that an inner swab rod in this example adopts the inner swab rod prepared in Comparative Example 2, and the rest is the same as Example 1.
[0131] Example 7
[0132] An environmentally friendly sampling swab is disclosed, which differs from Example 1 in that an outer swab rod and an outer sampling head in this embodiment are the outer swab rod and an outer sampling head prepared in Comparative Example 3, and the rest are the same as in Example 1.
[0133] Example 8
[0134] An environmentally friendly sampling swab is provided, which differs from Example 1 in that the outer swab rod and the outer sampling head in this embodiment adopt the outer swab rod and the outer sampling head prepared in Comparative Example 4, and the rest are the same as Example 1.
[0135] According to the standard GB / T 1040-2006, the tensile properties were tested, and the tensile strength of the inner swab rods prepared in Preparation Example 1-1, Preparation Example 1-2, Comparative Example 1, and Comparative Example 2 were tested respectively;
[0136] According to the standard GB / T 9341-2008, the bending strength test was carried out on the inner swab rods prepared in Preparation Example 1-1, Preparation Example 1-2, Comparative Example 1, and Comparative Example 2, respectively; the test results are shown in Table 1.
[0137] According to the standard GB / T 1043-2008, the impact strength test was carried out on the inner swab rods prepared in Preparation Example 1-1, Preparation Example 1-2, Comparative Example 1, and Comparative Example 2, respectively; the test results are shown in Table 1.
[0138] Table 1 Tensile strength, bending strength and impact strength tests of each inner swab rod
[0139] Performance Project Tensile strength (MPa) Bending strength (MPa) Impact strength (KJ / m2) Preparation Example 1-1 68.5 92.9 10.6 Preparation Example 1-2 67.1 89.5 9.3 Comparative Example 1 51.2 78.3 6.9 Comparative Example 2 48.5 73.0 5.1
[0140] It can be seen that the inner swab rods prepared in Preparation Example 1-1 and Preparation Example 1-2 have excellent mechanical properties, and their tensile strength, bending strength, and impact strength are much better than those of conventional sampling swabs and the inner swabs of Comparative Example 1 and Comparative Example 2. They are suitable for being made into strip materials for use in the present sampling swab, ensuring the shape, toughness and hardness of the present sampling swab, and also ensuring that the inner swab rod of the sampling swab prepared in Example 1-4 can be well abutted against the inner sampling head, and the biological samples (including tissue fluid, cells, etc.) collected on the sampling convex part of the inner sampling head and the outer sampling head are squeezed out for detection, thereby expanding the amount of samples collected and facilitating obtaining more accurate sampling detection results; at the same time, the inner swab rods prepared in Preparation Example 1-1 and Preparation Example 1-2 have good degradability and are environmentally friendly.
[0141] Performance test 2
[0142] According to GB / T1040-2006, the tensile properties were tested, and the tensile strength of the outer swab rods and outer sampling heads prepared in Preparation Example 2-1, Preparation Example 2-2, Comparative Example 3, and Comparative Example 4 were tested respectively; the test results are shown in Table 2.
[0143] According to GB / T29249-2012, the moisture content test was carried out. 10g of the prepared outer swab rod and outer sampling head samples were taken respectively and placed in the moisture analyzer. The drying temperature of the moisture analyzer was set to 100°C and the drying time was set to 20min. The moisture content of the sample was calculated based on the weight change of the outer swab rod and the outer sampling head samples before and after. The formula is as follows:
[0144]
[0145] Where w is the water content, the initial mass is m0, and the mass after drying is m1; the test results are shown in Table 2.
[0146] Table 2 Tensile strength and moisture content test of each external swab rod and external sampling head
[0147] Project Performance Tensile strength (MPa) Water content (%) Preparation Example 2-1 364.3 10.1 Preparation Example 2-2 326.4 11.7 Comparative Example 3 116.1 21.9 Comparative Example 4 113.7 25.2
[0148] It can be seen that the outer swab rod and the outer sampling head prepared in Preparation Example 2-1 and Preparation Example 2-2 have good mechanical properties and good water retention properties, are suitable for being made into strip materials, and have a certain elasticity for use in the present sampling swab. It also ensures that the outer swab rod and the outer sampling head prepared in Example 1-4 have a certain softness, which relaxes the user's psychology to a certain extent and facilitates tight fitting and pressing of the inner swab rod. The outer swab rod and the outer sampling head are repeatedly stretched and cycled many times, and their elasticity will not show obvious mechanical fatigue. At the same time, the outer swab rod and the outer sampling head prepared in Preparation Example 2-1 and Preparation Example 2-2 have good degradability and are environmentally friendly.
[0149] The biological samples collected from each sample in Examples 1-8 are sent for testing;
[0150] The environmentally friendly sampling swabs prepared in Examples 1-4 have an external sampling head that collects biological samples, taking the number of cells collected as an example, which is more than 30 times the biological samples collected by conventional commercially available sampling swabs (taking the number of cells collected as an example);
[0151] Examples 5-6 are still made using the preparation method of the external sampling head of the present scheme. Therefore, the biological samples collected by the external sampling head, taking the number of collected cells as an example, are more than 30 times the biological samples collected by the commercially available conventional sampling swabs (taking the number of collected cells as an example); many commercially available conventional sampling swabs are flocked swabs, sponge swabs, fiber swabs, etc.
[0152] The biological samples collected on the external sampling heads of Examples 7-8 are not as good as the external sampling heads made in Examples 1-8. Therefore, taking the number of collected cells as an example, the biological samples collected by commercially available conventional sampling swabs are 10 to 30 times (taking the number of collected cells as an example).
[0153] It can be seen that the environmentally friendly sampling swabs prepared in Examples 1 to 4 have several sampling convex portions, which expand the sampling surface area and facilitate the collection of more biological samples. The user inserts the environmentally friendly sampling swab into the mouth, throat or nose and close to the inner wall, and rotates it a few times. There is no need to poke it deep into the mouth, throat or nose or everywhere, and there is no need to repeatedly scrape the inner wall. While improving the user's comfort, it also reduces the sampling time; several sampling convex portions are processed from CNFs / CA / CMC-Na aerogel on the market, have good water absorption performance, better elasticity than the outer sampling head, and less tensile strength than the outer sampling head. Therefore, when the user samples inside the mouth, throat or nose, multiple sampling convex portions will quickly absorb the biological sample. When the sampling convex portion is squeezed by the inner swab rod, the biological sample collected on the inner sampling head will be quickly squeezed out for easy detection.
[0154] The above are only preferred specific implementation modes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An environmentally friendly sampling swab, characterized in that: The invention comprises an inner swab rod (1), an outer swab rod (2), an outer sampling head (3) and an inner sampling head (4); the outer sampling head (3) is fixedly provided at the upper end of the outer swab rod (2); the outer swab rod (2) and the outer sampling head (3) are hollow structures; the inner swab rod (1) is embedded in the inner part of the outer swab rod (2); a plurality of sampling grooves are provided at a certain interval at the sampling end of the outer sampling head (3); the inner sampling head (4) is arranged inside the outer sampling head (3); a plurality of sampling convex parts (41) are fixedly provided at the sampling end of the inner sampling head (4) at a certain interval; the plurality of sampling convex parts (41) are respectively penetrated and extend out of the plurality of sampling grooves; the sampling convex parts (41) slightly extend out of the sampling grooves; The inner swab rod (1) comprises the following raw materials in parts by weight: 95-105 parts of polylactic acid, 4-10 parts of polyhydroxyalkanoate, 15-40 parts of bamboo fiber, 5-8 parts of coconut shell fiber, 0.3-3 parts of silane coupling agent, 0.5-7 parts of maleic anhydride, and 0.2-0.8 parts of dicumyl peroxide; The outer swab rod (2) and the outer sampling head (3) comprise the following raw materials in parts by weight: 3 to 10 parts of sodium alginate, 30 to 90 parts of cassava starch and 15 to 45 parts of anhydrous calcium chloride; The inner swab rod (1) is made of cellulose aerogel; The preparation method of the inner swab rod (1) is as follows: Drying: Place bamboo fiber, coconut shell fiber, polylactic acid and polyhydroxyalkanoate in a constant temperature drying oven and fully dry them at a drying temperature of 60 to 90°C for 20 to 30 hours; Composite fiber synergistic surface modification, alkali treatment: Add the dried bamboo fiber and coconut shell fiber to a 5% sodium hydroxide solution according to a certain solid-liquid ratio, mix thoroughly, soak at room temperature for 10 to 15 hours, filter out, wash with deionized water until neutral, and put in a drying oven to fully dry at a drying temperature of 70 to 80°C for 6 to 8 hours; Composite biodegradable materials synergistic surface modification, silane coupling agent modification: The silane coupling agent KH560 is added to the mixture of ethanol and water in a certain volume ratio, and the pH thereof is adjusted to 5 with acetic acid, and the mixture is fully stirred with a magnetic stirrer. When no floccules appear in the mixture, the hydrolysis is completed; the alkali-treated and dried bamboo fiber and coconut shell fiber are added to the hydrolysis solution in a certain ratio, and the mixture is fully stirred again with a magnetic stirrer. After the stirring is completed, the mixture is placed in a ventilated place to wait for the volume to completely evaporate; Graft modification of polylactic acid and polyhydroxyalkanoate: Take maleic anhydride and dicumyl peroxide, dissolve them in a certain amount of acetone, the amount of acetone is appropriate to completely dissolve maleic anhydride and dicumyl peroxide; then add polylactic acid and polyhydroxyalkanoate, wait for the solvent to evaporate completely, use a torque rheometer to perform melt mixing, the mixing temperature is 170-185°C, the rotation speed is 30r / min, the mixing time is 12-15min, and finally obtain a graft copolymer product; Extrusion molding: The composite fiber that has been synergistically surface modified and the graft copolymer product that has been modified by a silane coupling agent are respectively placed into two feed ports of a twin-screw extruder, and appropriate feed speeds and screw speeds are set. The temperature from the feed port to the die outlet of the twin-screw extruder is set to 165-175° C., and finally a degradable high-strength strip is made, which is processed to form an inner swab rod (1).
2. The environmentally friendly sampling swab according to claim 1, characterized in that: In the alkali treatment, the solid-to-liquid ratio of the dried bamboo fiber and coconut shell fiber to the sodium hydroxide solution is 1:15-20.
3. The environmentally friendly sampling swab according to claim 1, characterized in that: In the silane coupling agent modification, the volume ratio of silane coupling agent KH560: ethanol and water mixed liquid is 1:6-15.
4. The environmentally friendly sampling swab according to claim 1, characterized in that: In the silane coupling agent modification, the solid-liquid ratio of the alkali-treated and dried bamboo fiber and coconut shell fiber to the hydrolysis solution is 1:5-8.
5. The environmentally friendly sampling swab according to claim 1, characterized in that: The preparation method of the outer swab rod (2) and the outer sampling head (3) is as follows: Preparation of sodium alginate solution: Sodium alginate is added into deionized water according to a certain solid-liquid ratio, and the sodium alginate solution is stirred evenly using a magnetic stirrer; Sodium alginate solution and tapioca starch mixing: Adding cassava starch to the sodium alginate solution, and stirring the mixture of cassava starch and sodium alginate solution evenly with a magnetic stirrer; placing the mixture of cassava starch and sodium alginate solution on a heating platform for heating at a temperature of 60 to 80° C. for 30 minutes to 1 hour until the mixture is fully mixed and becomes evenly distributed; and then placing the mixture under ultrasonic vibration to remove bubbles; Preparation of calcium chloride solution: Add anhydrous calcium chloride to deionized water according to a certain solid-liquid ratio, and stir thoroughly with a magnetic stirrer; stir the anhydrous calcium chloride and deionized water thoroughly at room temperature for 15 to 30 minutes; place them under ultrasonic vibration to remove bubbles and wait for them to return to normal temperature; Prepare the outer swab shaft (2) and the outer sampling head (3): After the sodium alginate solution and the calcium chloride solution are prepared, the prepared cassava starch / sodium alginate / calcium chloride solution is mixed evenly, degassed and poured into a mold, and left for a period of time to obtain a strip gel; then heated in a water bath at 60 to 80° C. for 15 to 30 minutes, and then the excess calcium chloride solution on the surface of the strip gel is washed off with deionized water, and then soaked in deionized water for 12 to 15 hours; finally, the soaked strip gel is placed in a freezer at a freezing temperature of -20 to -30° C. and a freezing time of 12 to 18 hours, and a strip hydrogel with good mechanical properties is obtained after freeze drying, which is processed to form an external swab rod (2) and an external sampling head (3).
6. The environmentally friendly sampling swab according to claim 5, characterized in that: In the preparation of the sodium alginate solution, the solid-to-liquid ratio of sodium alginate to deionized water is 0.03-0.1:
1.
7. The environmentally friendly sampling swab according to claim 5, characterized in that: In the preparation of the calcium chloride solution, the solid-to-liquid ratio of anhydrous calcium chloride to deionized water is 0.05-0.15:
1.
8. A method for preparing an environmentally friendly sampling swab according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: Sampling swab assembly The prepared inner sampling head (4) is placed inside the outer sampling head (3); the sampling protrusions of the inner sampling head (4) are respectively penetrated and extended through a plurality of the sampling grooves; the outer portions of the sampling protrusions of the inner sampling head (4) slightly extend out of the sampling grooves; the outer swab rod (2) and the outer sampling head (3) are connected by glue; finally, the inner swab rod (1) is tightly inserted into the inner portion of the outer swab rod (2), and the inner swab rod (1) and the inner sampling head (4) are in contact with each other.
Citation Information
Patent Citations
Nasopharyngeal swab with end adjusting function
CN213217222U
Sampling swab
CN221205485U